Acceptability of a microfinance‐based empowerment intervention for transgender and cisgender women sex workers in Greater Kuala Lumpur, Malaysia. Issue 1 (2nd August 2017) - Lall, Priya; Shaw, Stacey A.; Saifi, Rumana; Sherman, Susan G.; Azmi, Nuruljannah Nor; Pillai, Veena; El‐Bassel, Nabila; Kamarulzaman, Adeeba; Wickersham, Jeffrey A.
Abstract: Introduction : Cisgender and transgender woman sex workers (CWSWs and TWSWs, respectively) are key populations in Malaysia with higher HIV‐prevalence than that of the general population. Given the impact economic instability can have on HIV transmission in these populations, novel HIV prevention interventions that reduce poverty may reduce HIV incidence and improve linkage and retention to care for those already living with HIV. We examine the feasibility of a microfinance‐based HIV prevention intervention among CWSW and TWSWs in Greater Kuala Lumpur, Malaysia. Methods : We conducted 35 in‐depth interviews to examine the acceptability of a microfinance‐based HIV prevention intervention, focusing on: (1) participants' readiness to engage in other occupations and the types of jobs in which they were interested in; (2) their level of interest in the components of the potential intervention, including training on financial literacy and vocational education; and (3) possible barriers and facilitators to the successful completion of the intervention. Using grounded theory as a framework of analysis, transcripts were analysed through Nvivo 11. Results : Participants were on average 41 years old, slightly less than half (48%) were married, and more than half (52%) identified as Muslim. Participants express high motivation to seek employment in other professions as they perceived sex work as not a "proper job" with opportunities for career growth but rather as a short‐term option offering an unstable form of income. Participants wanted to develop their own small enterprise. Most participants expressed a high level of interest in microfinance intervention and training to enable them to enter a new profession. Possible barriers to intervention participation included time, stigma, and a lack of resources. Conclusion : Findings indicate that a microfinance intervention is acceptable and desirable for CWSWs and TWSWs in urban Malaysian contexts as participants reported that they were ready to engage in alternative forms of income generation.